PENGARUH INTELLECTUAL CAPITAL, KEPUTUSAN INVESTASI, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Donna Yessi Aprilia; Ika Kristianti; Jean Stevany Matitaputty (Jurnal Akuntansi dan Pajak, 2023)
The high value of the company makes the market believe in the prospects of the company. One of the most important problems for the management of a company is to identify the factors driving the value of the company. Most companies recognize that some part of their capital comes from creating value for investors. The value of the company itself is often seen from the share price of the company. This study aims to see whether intellectual capital, investment decisions, and dividend policy have an effect on firm value. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) respectively during the 2017-2021 period. There are 103 companies or 515 research observations that are included in this study. This study uses a purpose sampling technique. And use the SPSS application to process the influence of intellectual capital, investment decisions, and dividend policy on firm value. The results showed that intellectual capital and dividend policy had an effect on firm value, while investment decisions had no effect on firm value.